2015
DOI: 10.2116/analsci.31.1155
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive and Multiple Enzyme Activity Assay Using Reagent-release Capillary-Isoelectric Focusing with Rhodamine 110-based Substrates

Abstract: In this study, a simple and highly sensitive enzyme activity assay based on reagent-release capillary-isoelectric focusing is described. Reagent-release capillaries containing a fluorescent substrate, which produces fluorescent products possessing an isoelectric point after reaction with enzymes, provides a simple procedure. This is because it allows to spontaneously inject a sample solution into the capillary by capillary action, mixing reagents, and subsequently concentrating the fluorescent products based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In CIEF with RRGs, the profile of the formed pH gradient was almost the same as that obtained using the acid and base solutions. These results shows that the proposed RRGs are applicable to bioassays using CIEF with RRCs [25], which will realize a rapid, simple and easy-to-use bioassay based on RRC-IEF.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…In CIEF with RRGs, the profile of the formed pH gradient was almost the same as that obtained using the acid and base solutions. These results shows that the proposed RRGs are applicable to bioassays using CIEF with RRCs [25], which will realize a rapid, simple and easy-to-use bioassay based on RRC-IEF.…”
Section: Resultsmentioning
confidence: 75%
“…Yang et al [20,21] and Zhu et al [22,23] reported the immobilization of carrier ampholytes (CAs) on a monolithic column in the microchannel, thereby avoiding the addition of carrier ampholytes into the sample solution to prevent current increase. In our previous study, we reported that the use of a "reagent-release capillary" (RRC) facilitated the MIEF procedure simply by introducing a sample solution into a capillary via capillary action, soaking the cathodic and anodic ends of the capillary into basic and acid solutions filled in reservoirs, respectively, and applying an electric field [24,25]. However, this technique still requires a step of manual application of the acid and base solutions to the reservoirs after sample introduction into the RRC.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we found that N , N ′‐dipropionyl rhodamine pro‐fluorophore showed bright, cytoplasmic fluorescence in PLE‐expressing cells thus demonstrating suitability for cellular imaging. Recently, Lavis and others have demonstrated the utility of PLE for activating rhodamine‐based pro‐fluorophores using the tri‐methyl lock approach and recently re‐evaluated prior work with rhodamines released by serine hydrolase with varying peptide pro‐fluorophore scaffolds . Although compound 1 b had been previously prepared testing of 1 b as a substrate for PLE was not reported.…”
Section: Figurementioning
confidence: 99%
“…This property is used in the synthesis of photoactivable rhodamine analogues [ 48 ] and to synthesize fluorogenic substrates when studying the mechanisms of enzyme catalysis. Rhodamine 110 derivatives have been used as substrates to determine the activity of various enzymes [ 49 ]. Hybrid fluorophores consisting of a polypeptide-linked quantum dot and rhodamine that can be cleaved by caspase-1 have been used in apoptosis assays [ 50 ].…”
Section: Properties Of Synthetic Fluorophoresmentioning
confidence: 99%